ASEAN's efforts and Indonesia's strategy in dealing with the South China Sea conflict - Putri, Marsya Iftitah Audry; Argenti, Gili; Gustianti, Nurbani Adine (Peneliti.net, 2024)
The South China Sea is the basis of geopolitics in the Asia Asific region which has become a topic of international discussion, therefore the cause has provoked problems between several big countries in Asia and a number of member countries from ASEAN. The problem began with unilateral claims made by China against areas in the South China Sea which were considered illegal and carried out unilaterally. This prompted ASEAN to intervene in representing the disputed issue. In this article I will describe the role of ASEAN in responding to the conflict in the South China Sea and analyze Indonesia's role in the conflict even though Indonesia itself is neutral. The research method that I will use in this research is a qualitative method which functions to collect data and information analytical descriptive. Keywords : Indonesia, ASEAN, South China Sea, Territorial Disputes